Information-to-free-energy conversion: Utilizing thermal fluctuations - Toyabe, Shoichi (Biophysics (Nagoya-shi), 2013)
Maxwell’s demon is a hypothetical creature that can convert information to free energy. A debate that has lasted for more than 100 years has revealed that the demon’s operation does not contradict the laws of thermodynamics; hence, the demon can be realized physically. We briefly review the first experimental demonstration of Maxwell’s demon of Szilard’s engine type that converts information to free energy. We pump heat from an isothermal environment by using the information about the thermal fluctuations of a Brownian particle and increase the particle’s free energy.